Inflammation and lipid metabolism as a strong background connecting psoriasis and liver diseases - Kozłowska, Dorota; Myśliwiec, Hanna; Flisiak, Iwona (Dermatology Review/Przegląd Dermatologiczny, 2020)
Psoriasis is not an isolated pathology of the skin and joints, but is also characterized by multiple extracutaneous systemic manifestations. Beside the co-occurrence of obesity, arterial hypertension, dyslipidemia, and type 2 diabetes mellitus, there is a strong correlation with many liver disturbances. The most common liver comorbid disease coexisting with psoriasis is non-alcoholic fatty liver disease, which is a hepatic manifestation of metabolic syndrome. Both diseases share the same molecular mechanisms: chronic systemic inflammation, oxidative stress, disturbances of lipid metabolism, immune pathways and secretions of bioactive molecules. Additionally, patients with psoriasis have an increased risk of developing autoimmune liver disease and also liver cancer in comparison to the heathy population. Moreover, drugs used in treatment of psoriasis and psoriatic arthritis augment the hepatotoxic effect on the liver. The study below presents the most recent data on the liver diseases and their pathogenesis in patients with psoriasis.